MDRD, CKD-Epi and Creatinine Clearance with 24-Hour Urine Collection Results in Patients with Chronic Kidney Disease - Siti Nurul Hapsari; Leonita Anniwati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Kidney disease is a global public health problem, affecting over 750 million people worldwide. Glomerular Filtration Rate(GFR), which is calculated by measuring the creatinine clearance with 24-hour urine collection (CC) can be inaccurate due toimproper urine collection, causing the need for an easier and accurate method of calculation. This study was anobservational analytical cross-sectional research using consecutive retrospective sampling. Samples were data of patientswith Chronic Kidney Disease (CKD) who underwent CC test at the Clinical Pathology Laboratory of the Dr. Soetomo HospitalSurabaya during September-October 2018. Data were compared with the results of Cockcroft-Gault (CG), MDRD, andCKD-Epi formula, and were analyzed using the one-sample Kolmogorov-Smirnov test, paired T-test, and Wilcoxon SignedRank test. Correlation of CC results with CG, MDRD, and CKD-Epi results was tested with Spearman's rho and Bland Altmantest. The difference test of CC with CG, MDRD, and CKD-Epi showed results of (p=0.000), (p=0.194), and (p=0.468),respectively. There were significant differences between CC compared to CG, but not MDRD and CKD-Epi. There was amoderate correlation between CG, MDRD, CKD-Epi, and CC with r=0.529; 0.448, and 0.463, respectively. The mostcompatible formula was CKD-Epi. The measurement of GFR with CC correlated with CG, MDRD, and CKD-Epi; therefore, theycould be used as an alternative method to calculate GFR. Further experiments using an exogenous marker should beperformed to determine a suitable eGFR formula according to the degree of damage to the kidney.